Flows of walking and running pedestrians in a corridor through exits of different widths - Ren, Xiangxia; Zhang, Jun; Song, Weiguo (Safety science, 2021)
•The walking and running pedestrian flows through exits of different widths are studied.•The relatively free (constrained) phase is found when the density is lower (higher) than 1.65 m−2.•The flow rate differences of the walking and running flows decrease as the exit narrows.•The running flow is associated with longer distance headway in the corridor. Human safety in crowded environments has been recognized as an important and rapidly growing research area due to its significant implications for public safety. In this study, a series of experiments were performed in a 10 m long corridor to investigate the walking and running pedestrian flows. A piecewise linear decreasing trend is found between the pedestrian density and the corresponding speed difference with the critical density of 1.65 m−2. In the relatively free phase (density < 1.65 m−2), the speed difference decreases significantly with the slope of 0.77. Whereas, the difference remains small with a slope of 0.15 in the constrained phase (density > 1.65 m−2). In the corridor (excluding the 2 m area around the exit), running pedestrians show longer distance headways than the walking ones under relatively low-density situation. Meanwhile, the running flow is more continuous with a lower probability of clogging at the exit in the free phase. In reality, pedestrian density should be an important factor for a decision maker when deciding to take the walking or running evacuation strategy. The data also can be used as validation benchmarks for models that intend to simulate pedestrians evacuating through a corridor in the running way.